Respuesta :

41625

Answer:

Step-by-step explanation:

Simplifying

2.1x + -5.7 = 3.9(4.3 + -1.8x)

Reorder the terms:

-5.7 + 2.1x = 3.9(4.3 + -1.8x)

-5.7 + 2.1x = (4.3 * 3.9 + -1.8x * 3.9)

-5.7 + 2.1x = (16.77 + -7.02x)

Solving

-5.7 + 2.1x = 16.77 + -7.02x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '7.02x' to each side of the equation.

-5.7 + 2.1x + 7.02x = 16.77 + -7.02x + 7.02x

Combine like terms: 2.1x + 7.02x = 9.12x

-5.7 + 9.12x = 16.77 + -7.02x + 7.02x

Combine like terms: -7.02x + 7.02x = 0.00

-5.7 + 9.12x = 16.77 + 0.00

-5.7 + 9.12x = 16.77

Add '5.7' to each side of the equation.

-5.7 + 5.7 + 9.12x = 16.77 + 5.7

Combine like terms: -5.7 + 5.7 = 0.0

0.0 + 9.12x = 16.77 + 5.7

9.12x = 16.77 + 5.7

Combine like terms: 16.77 + 5.7 = 22.47

9.12x = 22.47

Divide each side by '9.12'.

x = 2.463815789

Simplifying

x = 2.463815789

where’s my money , lol jokes
ACCESS MORE